Coastal Hazards of Tropical‐Like Cyclones Over the Mediterranean Sea. Issue 2 (22nd February 2022) - Toomey, Tim; Amores, Angel; Marcos, Marta; Orfila, Alejandro; Romero, Romualdo
Abstract: Medicanes, for Mediterranean hurricanes, are mesoscale cyclones with morphological and physical characteristics similar to tropical cyclones. Although less intense, smaller, and rarer than their Atlantic counterparts, medicanes are very hazardous events threatening islands and continental coasts within the Mediterranean Sea. The latest strong episode, Medicane Ianos (September 2020), resulted in severe damages in Greece and several casualties. This work investigates the oceanic response to these extreme events along the Mediterranean coasts under present‐day and future (late 21st century) climate conditions. To this end, a coupled hydrodynamic‐wave model is used to simulate both storm surges and wind‐waves generation and propagation in the Mediterranean Sea at high resolution (∼2 km) along the coastlines. A data set of thousands of medicanes synthetically generated from 20 global climate models and two atmospheric reanalyses is used to derive the atmospheric forcing fields. Regional coastal hazards assessment is performed for the present and future climates. For the first period, highest medicane‐induced waves are found in the central and the southwest part of the western Mediterranean, while greatest storm surges are found in the Adriatic Sea and regions characterized by wide and gently sloping continental shelves. Results obtained for future changes show amplitudes generally smaller than the associated uncertainty due to limited agreement among models (especially for coastal elevation). Though, model consensus is reached (60–75%) and relative intensity change is significant (10–20%) at some locations (e.g., 1 m increase of medicane‐induced significant wave height on average for south coasts of Sicilia). Plain Language Summary: Mediterranean hurricanes, medicanes, are tropical‐like cyclones generated in the Mediterranean basin that differ from their counterpart in the Atlantic in their smaller size and intensity. They rarely exceed 400 km of diameter and last generally 24–48 hr, unusually reaching intensities of category 1 hurricanes. A medicane is characterized by a warm core accompanied by thunderstorms, heavy rain, but also strong cyclonic winds (counter‐clockwise rotation) that are responsible for costly damages and often result in casualties. Furthermore, medicanes pose serious threats to coastal populations due to the storm surges, that is, the raising of the sea surface due to low atmospheric pressure, and to the combined effects of waves and winds along the coasts. This study investigates the coastal hazards induced by medicanes over the entire basin. To do so, we used a hydrodynamic and wave coupled model to simulate the generation and propagation of storm surges and wind‐waves over the Mediterranean Sea under the forcing of a set of thousands of synthetic medicanes that statistically describe the medicane climate for the present and future period (end of 21st century). Our results identify the most exposed coastal areas and quantify the current and projected return levels for waves and storm surges. Key Points: Mediterranean hurricanes (medicanes) generate largest wind‐waves (exceeding 10 m) in the central and the southwest part of the western basin Wide and gently sloping continental shelves favor the generation of storm surges under medicane forcing with 100‐year return levels over 1 m Projected changes medicane‐induced coastal hazards are uncertain due to limited multimodel consensus, with some local exceptions